Правове регулювання процесуальної діяльності з проведення негласних слідчих (розшукових) дій та використання їх результатів у кримінальному провадженні - Смаглюк, С. В.; Smahliuk, S. V. (Наше право. - 2022. - № 4. - С. 211-218, 2022)
Доведено, що проведення негласних слідчих (розшукових) дій та використання їх результатів у кримінальному провадженні неможливе без належного правового регулюванні відповідних процесуальних відносин. Визначено, що правове регулювання відіграє роль правової гарантії законності таких дій та легітимності отриманих результатів. Наведено характеристику правового регулювання проведення негласних слідчих (розшукових) дій та використання їх результатів у кримінальному провадженні.

It has been proven that the conduct of covert investigative (search) actions and the use of their results in criminal proceedings is impossible without proper legal regulation of the relevant procedural relations. Attention is drawn to the fact that without such legal mediation, criminal procedural activity cannot be considered a legal means of ensuring a quick, complete and impartial investigation and trial. It is proposed to consider the legal regulation of undercover investigative (search) actions as a means of ensuring their legality and the way in which special subjects are empowered by state authority to conduct undercover investigative (search) actions and use their results in criminal proceedings. It was determined that legal regulation plays the role of a legal guarantee of the legality of secret investigative (search) actions and the legitimacy of the obtained results. For the procedural activity of conducting secret investigative (search) actions and using their results in criminal proceedings, the legal regulation will have its own specifics, namely: it will mainly be carried out using the special-permissive type, it will be carried out using the imperative method; the main means of such regulation are the norms of criminal procedural law. Based on the analysis of the points of view of scientists and acts of criminal procedural legislation, the characteristics of the mechanism of procedural legal regulation of secret investigative (search) actions and the use of their results in criminal proceedings are given. The opinion is substantiated that the emergence of the sectoral level of legal regulation is due to the peculiarities of the content and the specificity of the nature of behavior, as well as the composition of the participants in procedural relations, which provides for the regulation of these legal relations thanks to the action of the corresponding mechanism of procedural regulation. It has been proven that the main means of regulating criminal procedural activities for conducting undercover investigative (search) actions and using the obtained results are criminal procedural norms, which have found their formal consolidation in criminal procedural legislation. The point of view is expressed that the nature of the action of the elements of the mechanism of procedural legal regulation simultaneously ensures both the effectiveness of criminal proceedings in terms of the use of the results of secret investigative (search) actions, as well as the protection of the rights, freedoms and legitimate interests of its participants. According to its meaning, the procedural legal regulation of the use of the results of secret investigative (search) actions in criminal proceedings acts as a guarantee in criminal proceedings.

Доказано, что проведение негласных следственных (розыскных) действий и использование их результатов в уголовном производстве невозможно без должного правового регулирования соответствующих процессуальных отношений. Определено, что правовое регулирование играет важную роль правовой гарантии законности таковых действий и легитимности полученных результатов. Приведена характеристика правового регулирования проведения негласных следственных (розыскных) действий и использование их результатов в уголовном производстве.
Keywords: правове регулювання; legal regulation; правовое регулирование; негласні слідчі (розшукові) дії; secret investigative (research) actions; негласные следственные (розыскные) действия; процесуальна діяльність; procedural activity; процессуальная деятельность; кримінальне провадження; criminal proceedings; уголовное производство; кримінальне процесуальне законодавство; criminal procedural legislation; уголовное процессуальное законодательство